Amino acid sequence of tyrosinase from Neurospora crassa. - Lerch, K (1978)
The amino-acid sequence of tyrosinase from Neurospora crassa (monophenol,dihydroxyphenylalanine:oxygen oxidoreductase, EC 1.14.18.1) is reported. This copper-containing oxidase consists of a single polypeptide chain of 407 amino acids. The primary structure was determined by automated and manual sequence analysis on fragments produced by cleavage with cyanogen bromide and on peptides obtained by digestion with trypsin, pepsin, thermolysin, or chymotrypsin. The amino terminus of the protein is acetylated and the single cysteinyl residue 96 is covalently linked via a thioether bridge to histidyl residue 94. The formation and the possible role of this unusual structure in Neurospora tyrosinase is discussed. Dye-sensitized photooxidation of apotyrosinase and active-site-directed inactivation of the native enzyme indicate the possible involvement of histidyl residues 188, 192, 289, and 305 or 306 as ligands to the active-site copper as well as in the catalytic mechanism of this monooxygenase.